The Application of Speech Repair Strategies by EFL Students in Speaking Class - Sholihah, Miftakhul Naimatu; Laila, Malikatul (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to explore effective strategies for implementing character education in the digital era by focusing on the roles of schools, parents, and students. It addresses the evolving challenges faced by parents as primary educators in shaping student character amidst rapid technological Methodology: The research adopts a qualitative case study approach and is supplemented by a questionnaire to gather data. It captures the general understanding and perspectives of parents and students regarding character education in the digital context. Results: The findings show that parents possess a high level of awareness and commitment to digital character education for high school students. Many parents understand their responsibilities and view technology positively as a supporting tool. Nevertheless, issues such as inconsistent digital supervision and varying levels of parental involvement present ongoing challenges. Some parents attempt to manage this by setting rules and limiting gadget use at home. Applications/Originality/Value: This study highlights the critical role of collaboration between schools and parents in promoting digital character education. It emphasizes that active parental involvement not only supports students' academic performance but also contributes to their social-emotional development. The insights offered may inform the development of structured programs to enhance parent-school cooperation, although the study's findings are subject to the limitations inherent in self-reported data.